Studi Komprehensif Keamanan Siber: Perbandingan Teknologi AI dengan Sistem Non-AI dalam Deteksi dan Pencegahan Ancaman - Santika, Yollandaru Yoga; Rianto, Rianto; Ujianto, EIH (Universitas Muhammadiyah Magelang, 2025)
This research examines cybersecurity approaches in Indonesia, focusing on the implementation of Artificial Intelligence (AI) technology compared to non-AI systems in detecting and preventing threats. The study identifies the advantages of AI, such as its capabilities in large-scale data analysis, detection of suspicious patterns, and reduction of human error. The methodology follows PRISMA guidelines for systematic literature review. Findings reveal that while AI can enhance threat detection effectiveness and resilience against attacks, the adoption of this technology in Indonesia remains limited by infrastructure, resources, and technical expertise. This research is expected to provide insights for more proactive national cybersecurity policies and support the development of AI technology in future information security initiatives.